Limitations of Technology Utilization in PAI Learning Evaluation at MTs Annihayah Karawang Based on Modern Islamic Boarding Schools - Dhika Gitaris Meliawan; Anisa Rizkiani; Auli Azzahra; Faiha Nur Haya; Shofiyana Nadia Fairuz (Annujum: Journal of Humaniora and Law, 2026)
This study aims to describe the limitations of technology utilization in the evaluation of Islamic Religious Education (PAI) learning at MTs Annihayah Rawamerta Karawang, identify the factors causing such limitations, analyze their impacts on the evaluation process, and examine teachers' strategies in optimizing learning evaluation. This study employed a qualitative field research approach. Data were collected through observation, interviews, and documentation involving PAI teachers. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the use of technology in PAI learning evaluation is still limited due to pesantren policies restricting students from using personal electronic devices. Consequently, most evaluation activities are conducted through written tests, oral tests, assignments, and observation. These limitations affect the efficiency of evaluation, feedback delivery, and the variety of assessment instruments. However, teachers continue to optimize evaluation through authentic assessment, continuous observation, varied assignments, and the utilization of available school facilities. The study concludes that the quality of learning evaluation is determined not only by technology use but also by teachers’ ability to design and implement appropriate assessment strategies.